5B.05: MARFAN SYNDROME. (June 2015) - Grillo, A.; Pini, A.; Marelli, S.; Gan, L.; Giuliano, A.; Trifirò, G.; Santini, F.; Salvi, L.; Salvi, P.; Viecca, F.; Carretta, R.; Parati, G.
Abstract : Objective: Marfan syndrome is an autosomal dominant genetic disorder characterized by an abnormal fibrillin-1 synthesis. Aortic root dilation and dissection are the main problems affecting patients prognosis in these patients. Their pharmacological prophylaxis with losartan or with a beta-blocker counteracts the aortic root dilation, but a close follow-up is required to assess therapeutic response rate and to identify non-responders. Unfortunately genotype-phenotype studies do not allow to determine the exact risk profile in these patients and there is no reliable method to accurately predict their risk of aortic dissection. Aim of this study was to evaluate non-invasive markers for identification of Marfan patients at higher risk of aortic complications. Design and method: We studied 187 Marfan patients (identified according to 2010 Revised Ghent Criteria and positive genetic analysis), age 32.3 ± 16.5 yrs (mean ± SD). 52 patients (27.8%) had undergone surgical ascending aorta replacement (David or Bentall procedure). Central pressure curves were recorded by PulsePen tonometer, and the aortic viscoelastic aortic properties were studied by determination of carotid-femoral pulse wave velocity (PWV). Results: With reference to the age related distribution of PWV values in a normal population, defined according to Arterial-Stiffness-Collaboration, PWV mean values in Marfan patients corresponded to 60th percentile in non- operated patients and to the 67th percentile in those operated. Adult Marfan patients (n = 146) generally displayed a low blood pressure, because of the pharmacological prophylaxis, and were compared with a population of 189 adult healthy subjects (81 males), matched by age (38 ± 13 vs 38 ± 16 yrs.), heart rate (64 ± 9 bpm vs 64 ± 11 bpm) and blood pressure (mean BP = 78 ± 9 mmHg vs 79 ± 4 mmHg) values. Average PWV value was higher than in healthy controls (PWV = 7.0 ± 1.7) both in not operated (PWV = 7.6 ± 1.6; p = 0.0003) and in operated (PWV = 9.5 ± 3.2; p < 0.0001) Marfan patients. Among non operated patients, PWV was significantly correlated to aortic root diameters (Aortic annulus: R 2 = 0.14; Valsalva sinuses: R 2 = 0.22; Sinotubular junction: R 2 = 0.28). Conclusions: A significant reduction of the distensibility of the aorta was found in Marfan syndrome. Further analyses are needed to assess the prognostic significance of PWV changes seen in these in these patients.